2008
DOI: 10.1523/jneurosci.3194-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Cortical Mapping of Fractional Anisotropy in Developing Rat Brains

Abstract: Cortical development is associated with a series of events that involve axon and dendrite growth and synaptic formation. Although these developmental processes have been investigated in detail with histology, three-dimensional and quantitative imaging methods for rodent brains may be useful for genetic and pharmacological studies in which cortical developmental abnormalities are suspected. It has been shown that diffusion tensor imaging (DTI) can delineate the columnar organization of the fetal and early neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
80
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 45 publications
9
80
0
Order By: Relevance
“…In a recent publication of The Journal of Neuroscience, Huang et al (2008) reported that FA could be used to quantitatively map spatiotemporal patterns of cortical development in the rat brain. Although well investigated at the cellular level, cortical development during the early postnatal period remains largely unmapped across all cortical regions in the whole brain because of the practical limitations of histological methods.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent publication of The Journal of Neuroscience, Huang et al (2008) reported that FA could be used to quantitatively map spatiotemporal patterns of cortical development in the rat brain. Although well investigated at the cellular level, cortical development during the early postnatal period remains largely unmapped across all cortical regions in the whole brain because of the practical limitations of histological methods.…”
mentioning
confidence: 99%
“…To characterize whole-brain structural development, high-resolution DTI images of ex vivo rat brains were acquired at five time points during postnatal development [postnatal day 0 (P0), P3, P7, P11, and P19]. Using FA to index the degree of cortical columnar organization at single measurement points, the authors identified an age-dependent decrease in FA with regional specificity in the cortex [Huang et al (2008), their Fig. 4 (http://www.…”
mentioning
confidence: 99%
See 3 more Smart Citations